Preserving the Regional Language of Mongondow: A Contrastive Analysis of Word Formation Patterns and Persona Pronouns - Donal Matheos Ratu (English Education Department, 2025)
This study discusses the similarities and differences between persona pronouns in the regional languages of Mongondow and Indonesian in terms of form function and meaning as well as their implications on the learning of regional languages in schools in Bolaang Mongondow Regency The method used was a contrastive analysis with a qualitative descriptive approach which involved observation and interviews with 30 native bilingual speakers of Mongondow and Indonesian The results show that persona pronouns in both languages have fundamental morphological similarities and syntactic functions but the pragmatic context in Mongondow is richer and reflects local social and cultural values The research emphasizes the importance of understanding these differences and similarities as the basis for the development of effective local content teaching materials to support the preservation of regional languages In addition the results of the research are expected to encourage the integration of local content of the Mongondow language in competency based curricula in schools and motivate the younger generation to preserve regional languages This study also paves the way for further research to expand other linguistic aspects for the sustainable preservation of local culture This research makes a significant contribution to the development of regional language learning based on empirical data while strengthening local and national cultural identity< p>